If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -1(2x + 1) = 8 + -3x + 3 Reorder the terms: x + -1(1 + 2x) = 8 + -3x + 3 x + (1 * -1 + 2x * -1) = 8 + -3x + 3 x + (-1 + -2x) = 8 + -3x + 3 Reorder the terms: -1 + x + -2x = 8 + -3x + 3 Combine like terms: x + -2x = -1x -1 + -1x = 8 + -3x + 3 Reorder the terms: -1 + -1x = 8 + 3 + -3x Combine like terms: 8 + 3 = 11 -1 + -1x = 11 + -3x Solving -1 + -1x = 11 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -1 + -1x + 3x = 11 + -3x + 3x Combine like terms: -1x + 3x = 2x -1 + 2x = 11 + -3x + 3x Combine like terms: -3x + 3x = 0 -1 + 2x = 11 + 0 -1 + 2x = 11 Add '1' to each side of the equation. -1 + 1 + 2x = 11 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 11 + 1 2x = 11 + 1 Combine like terms: 11 + 1 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| (4x+8)+44+106=180 | | 9m-(3+2m)= | | 8x+34=360 | | (2x-13)+(4x+3)+(x+15)=180 | | 3(x-7)=-7 | | 7(7k+6)= | | 9y-2=4y+18 | | (2x-50)+(2x)+30=180 | | 48=-w+165 | | Y=x^2+x^6 | | 16x+80=48x+16 | | 6m-(3+4m)= | | 1.5x+6=11 | | 44=Y/2 | | 12t-4(t-5)=4 | | 15-u=224 | | 3b+4x*8c= | | 5-4[5-(3y-2)]= | | =27x^2+32x-32 | | (x-35)+(2x-35)+(x-34)=180 | | 9[7-(9-9r)]= | | 7w-2p=-25 | | -u+57=160 | | (-2x-3)+(5m+8x)+(4+9m)= | | =3x^2-10x+1 | | 4x+(2x+3)+(2x-1)=180 | | (x-3)(5+2x)-(x-3)(x-6)= | | (5x-1)/3=3 | | 2x+30=2x-30 | | 9s(7s+7)+s(3s+6)= | | 4-5[2-(4y-3)]= | | (2x+4)+(4x-15)+93=180 |